Answer:
[tex]x = \frac{k + c}{4}[/tex]
Step-by-step explanation:
Given:
[tex]4x - c = k[/tex]
Solve for:
[tex]x[/tex]
Solution:
(1) Let's move all of components that do not contain [tex]x[/tex] (our target) to the right side (notice the change of sign of [tex]c[/tex] from negative to positive):
[tex]4x = k + c[/tex]
(2) Let's divide both sides of equation by 4:
[tex]\frac{4x}{4} = \frac{k + c}{4}[/tex]
(3) Now, we simplify the left side:
[tex]x = \frac{k + c}{4}[/tex]
This is the solution.
Hope this helps!
:)